The influence of social supports to teenagers’ overall physical behavior changes towards physical activity / Rozita Abdul Latif … [et al.] - Abdul Latif, Rozita; Ahmad, Jamaliyah; Mohd Nor, Mohd Anizu; Ab Rahman, Zarizi (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This research was carried out to investigate the influence of the teenagers’ social supports gained that cause overall changes behaviors of them towards physical activity at the edge of the city within the district of Muar, Johor Darul Takzim. Samples of the research was total of 200, 118 of the male students and 82 of female students with age of 14.3 (SD =1.491). The result showed that the influence of the social supports to teenagers specifically on their involvement with physical activities make most significant (P < 0.05) consisted environment factors, physical activity benefits, self-efficacy and the barriers as well. The finding contributed implication of teenagers’ behavior changes with involvement with physical activities. Suggestion future research through qualitative with longitudinal method.